СОВРЕМЕННЫЕ МЕХАНИЗМЫ РАЗВИТИЯ ПРОФЕССИОНАЛЬНЫХ КОМПЕТЕНЦИЙ ПЕДАГОГА В ЭЛЕКТРОННОЙ ОБРАЗОВАТЕЛЬНОЙ СРЕДЕ - Джанабаева, А. (SCIENCE and SOCIETY, 2023)
The article reveals the features of the continuous development of professional competence in the professional training of teachers using innovative pedagogical and production technologies. It is proposed to use pedagogical technologies of distance and project-based learning, as well as advanced production technologies for the formation of professional competencies among participants in the educational process (teachers and students). The educational and methodological potential of learning technologies is revealed.
Keywords: mechanism; competence; digital environment; UNESCO; upbringing; education